Exploring Hindko Indexicals: A Pragmatic Analysis with Implications for Language Teaching - Javed, Mir Ahsan; Mahroof, Maqddus; Fayyaz, Muhammad Ashar; Rashid, Khawaja Umer (English Lecturers and Teachers Association (ELTA), 2024)
The study aims to address the challenges faced by English language teachers and learners in multilingual contexts by examining the deictic expressions in Hindko, an under-documented and endangered language. In a world where linguistic diversity is increasingly threatened, documenting lesser-known languages like Hindko becomes imperative to preserve cultural heritage and enrich linguistic understanding. This research focuses on the comparative analysis of deictic expressions in Hindko and English, specifically exploring person, spatial, and temporal deixis. By elucidating the differences between these languages' deictic systems, the study aims to equip English language teachers with insights into potential pitfalls Hindko-speaking learners may encounter when acquiring English deixis. Moreover, the research identifies common errors made by Hindko-speaking learners and provides strategies for addressing these challenges in English language teaching. Additionally, the study enhances linguistic knowledge by delving into the intricacies of marking numbers and gender on Hindko indexical, offering learners and language teachers a deeper understanding of linguistic diversity and cultural nuances. Through its findings, this research contributes to the broader scope of English Language Teaching by fostering cross-linguistic awareness, promoting cultural sensitivity, and enhancing language instruction in diverse educational settings. Keywords: Deixis; deictic expression_indexical.